Chapter England's Maritime and Commercial Networks in the Late Middle Ages - Childs, Wendy R. (Atti delle «Settimane di Studi» e altri Convegni, 2019)
This paper, basing its analysis on England's national customs accounts between the thirteenth and fifteenth centuries, briefly examines England's ports as commercial nodes (of which London was the busiest, with Hull, Southampton and Bristol becoming the main regional hubs by the fifteenth century), its shipping (which provided both liner and tramping services and sailed all year round), and its exports (which shifted from wool to woollen cloth over the period). It then focuses on the range of markets with which English merchants and ships had direct maritime contacts.